Ayurvedic Management Of Rheumatoid Arthritis (Aamvaat) -A Case Study - Sahu, Rishi (International Research Journal of Ayurveda & Yoga, 2020)
Acharya Madhavkar has describe Aamvaat which can be correlated with rheumatoid arthritis. Amavata is a chronic inflammatory disorder that can affect more on joints and can also damage a wide varsity of body system. Rheumatoid is an autoimmune disease it can attack whole body tissue. As per modern medicine Anti-inflammatory, analgesics, steroids, anti-rheumatic drugs are required for its management. Many herbal as well as Ayurvedic preparations are mentioned in the classics which are very effective remedy in Amavata. In this case study we after deepen pachana and snehapana, virechana karma was done by the administration of Trivrita avaleha and castor oil. After shodan karma a bunch of Ayurvedic medicine are given with oil for local application followed by potali svedana. The result of 90 day long treatment is concluded and discussed below.